The Effect of Marketing Mix Strategy on Increasing Sales Volume of Silk Cloth - Adnan Hasan (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to examine and analyze the influence of the marketing mix strategy consisting of (product, price, place and promotion) on the increase in sales volume of silk fabrics to Silk Craftsmen of BNI Sengkang Village, Wajo Regency. The population in this study is all people who use or buy silk cloth products from silk craftsmen in Kampung BNI Sengkang, Wajo Regency. The number of samples used in this study were 100 people. The data in this study used primary data obtained by distributing questionnaires to all respondents and through direct interviews with consumers. The data in this study will be tested with several stages of testing, namely descriptive statistical tests, validity and reliability tests and testing of all hypotheses through the coefficient of determination test, partial test (t test) and simultaneous test (f test). The results of this study indicate that the marketing mix consisting of the 4Ps (product, price, place, promotion) has a positive and significant effect on increasing silk sales to Silk Craftsmen of BNI Sengkang Village, Wajo Regency. Among the marketing mix, the price strategy has the most dominant influence on silk sales to Silk Craftsmen of BNI Sengkang Village, Wajo Regency, based on the results of statistical analysis, the value of the regression coefficient shows the highest value among the other independent variables.